Biochar as a renewable source for high-performance CO2 sorbent. (October 2016) - Li, Yilun; Ruan, Gedeng; Jalilov, Almaz S.; Tarkunde, Yash R.; Fei, Huilong; Tour, James M.
Abstract: Natural gas wells evolve CO2 along with the hydrocarbon stream. Because of the wide use of natural gas as an energy source, the emission of CO2 from high pressure natural gas wells is of concern. While various sorbents have been developed to purify natural gas, studies are lacking on the use of renewable biosources, especially biochar, to prepare porous carbon sorbents for CO2 capture at high pressure. Here we report the use of low-cost biochar as the feedstock for a one-step KOH activation towards high surface area solid state CO2 sorbents. Under the optimal activation conditions, a surface area of 3167 m 2  g −1 is reached with a CO2 uptake of 26.0 mmol g −1 (1.15 g g −1 ) at 30 bar and 25 °C. The cycling stability and CO2 /CH4 selectivity of the synthesized biochar-derived porous carbon have been evaluated, and activity screenings show that wood wastes pyrolyzed at a mid-range temperature, 450 °C, are the preferred type of biochar for use as high performance CO2 sorbents in high pressure applications. Graphical abstract: